PENGARUH KEMAMPUAN BAHASA ARAB TERHADAP PRESTASI MENGHAFAL AL-QUR’AN PADA SISWA SDIT MUHAMMADIYAH AL-KAUTSAR KARTASURA - Naura Rahma Dinda; Sabrina Hananti Nur Aini; Annisa Ardhiana Eka Putri; Afifah Khoirun Nisa; Miftakhul Khoiriyah; Rista Lutfianingsih (Publikasi Inspirasi Indonesia, 2025)
This research aims to identify the relationship between Arabic language skills and achievement in memorizing the Al-Qur'an among students at SDIT Muhammadiyah Al-Kautsar Kartasura. The research approach used is quantitative correlational with two main variables, namely mastery of Arabic as the independent variable (X) and achievement in memorizing the Al-Qur'an as the dependent variable (Y). The research sample consisted of 50 students selected based on certain criteria. Data collection was carried out through Arabic language proficiency tests, Al-Qur'an memorization assessments, as well as documentation of tahfidz report cards and academic report cards. The results of the analysis show that there is a significant relationship between Arabic language ability and achievement in memorizing the Al-Qur'an, with a correlation coefficient of r = 0.72, which shows a strong and positive relationship. Apart from that, simple linear regression analysis shows that mastery of Arabic contributes 51.8% to the achievement of memorizing the Qur'an, while the rest is influenced by other factors such as motivation, learning methods and learning environment. The implications of this research confirm that improving the quality of Arabic language learning plays an important role in supporting the effectiveness of students' memorization of the Al-Qur'an. Therefore, a more interactive and understanding-based learning approach is recommended to improve tahfidz results.